The efficiency of ultrasound-guided erector spinae plane block in early cervical cancer patients undergoing laparotomic radical hysterectomy: A double-blind randomized controlled trial - Zhou, Ling; Wang, Shan; Liu, Chunmei; Yan, Tingting; Song, Youping; Shu, Shuhua; Wang, Sheng; Wei, Xin (Frontiers in Surgery, 2023)
Aims We aim to compare the efficiency of erector spinae plane block (ESPB) with transversus abdominis plane block (TAPB) in patients undergoing laparotomic radical hysterectomy because only a few studies are reported exploring this matter. Methods In this randomized controlled trail, 154 eligible patients were randomly allocated into ESPB group [ESPB + patient-controlled intravenous analgesia (PCIA)] and TAPB group (TAPB + PCIA) at 1:1 ratio. The primary outcome was visual analog scale (VAS) score at rest state at 12 h. Results We found that ESPB group was associated with the lower VAS scores at rest and cough state than TAPB group at 2, 4, 6, 12, and 24 h postoperatively (P < 0.05). Less analgesic consumption and sufentanil consumption in PCIA pump were found in the ESPB group (P < 0.05). Moreover, ESPB group was followed by fewer rescue analgesia requirements, less rescue analgesic consumption, less adverse reactions, and higher analgesia satisfaction (P < 0.05). Conclusions Our study found that ESPB had advantages on analgesic effect and opioids consumption. In the future, more studies were needed to confirm our findings. Systematic Review Registration:https://www.chictr.org.cn/index.aspx, identifier: ChiCTR2100044240.